Some aspects of teaching elements in the Chinese language linguistic and cultural studies - Kenzhebaeva, A. A.; Daulet, F. N. (Journal of Oriental Studies, 2016)
It is considered in the article of the role of introduction of the linguistic and cultural studies in the process of teaching the Chinese language, the authors of the article gives the definition to the language parasitological units as information carrying about the peculiar norms of the Chinese society. It is given a clear analysis of some elements of linguistics and cultural studies which have to be implemented into teaching process.